An Analysis of the Effectiveness and the Contribution of Local Taxes and Local User Fees on the Local Own-Source Revenue Improvement in East Java - Febriana, Vania Salsabillah; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The performance of local revenue (PAD) is an indicator of the success of regional autonomy. To maximize regional autonomy and reduce dependence on the central government, local governments must increase own-source revenues, including local taxes and levies. This study aims to analyze the effectiveness and contribution of local taxes and local levies to PAD in East Java in the period 2018-2022. This research uses a quantitative approach with effectiveness and contribution ratio analysis. Based on the results of the research conducted, the researcher concluded that the effectiveness of local tax revenues of 38 cities / districts in East Java Province during the last 5 years, namely 2018-2022, was included in the category of quite effective to very effective with an average exceeding 80%, the effectiveness of local levy revenue of 38 cities / districts in East Java Province during the last 5 years, namely in 2018-2022 as a whole is included in the effective category with a value of 90.73%, the contribution to local tax revenue of 38 cities / districts in East Java Province during the last 5 years, namely in 2018-2022 as a whole is included in the category quite good with a value of 34.92%. The contribution of local levy revenue of 38 cities / districts in East Java Province during the last 5 years, namely in 2018-2022 as a whole, is included in the category of not good enough with a value of 34.92%.